Convergence rate sliding mode control of permanent magnet synchronous motor based on expanded sliding mode observer - Li Tian; Qingrui Wei; Qiang Zheng; Hailong Li (Journal of Engineering and Applied Science)
Abstract The aim is to address the limitations of conventional sliding mode control for PMSM, namely the problems of sliding mode oscillation, load disturbance, and poor control accuracy. An improved sliding mode control strategy for PMSM is proposed based on the novel convergence rate and extended state observer. Firstly, an integral sliding mode velocity loop controller is designed based on the novel convergence rate to solve the sliding mode vibration problem. The stability of the proposed control strategy is derived by the Lyapunov criterion. Secondly, an extended state observer capable of estimating the disturbance torque is designed for the purpose of disturbance compensation. The disturbance torque estimate is then used as a feed-forward signal for the sliding mode velocity loop controller. A fast second-order sliding mode controller is used for the current loop to avoid the potential introduction of noise and disturbances. The simulation results show that compared to alternative control strategies, the proposed control strategy enables the PMSM to respond effectively to start-up and load disturbances, significantly reduces the sliding mode jitter, and improves both the torque estimation accuracy and the system control accuracy.